Integrating Maja Labo Dahu culture in Islamic education: a module for character development in elementary students - Umar, Umar; Ghufron, Anik; Wuryandani, Wuri (Intelektual Pustaka Media Utama, 2025)
This study aims to measure the development of Islamic education modules integrated with Maja Labo Dahu culture that can improve the character of elementary school students. Module development was conducted at State Elementary School 45 Pane, Bima City, using the Borg and Gall model development research (RD) method. The results of the product validity test of the Maja Labo Dahu culture-integrated Islamic education module showed a score of 3.60, which was included in the very feasible criteria. Based on the results of the small group, limited-scale trial consisting of 20 students of State Elementary School 45 Pane, Bima City with a sample of 18 grade V students, it shows the effectiveness of improving student character in learning activities using Islamic education modules integrated with Maja Labo Dahu culture. The results of the data analysis of student character observations are also in the good category, with an average value of 3.33. We know that 50% of students meet the good attitude criteria. Thus, the development of Islamic education teaching modules integrated with Maja Labo Dahu culture has a positive impact on improving the character values of elementary school students.